Atom probe tomographic assessment of the distribution of germanium atoms implanted in a silicon matrix through nano-apertures. (31st August 2017) - Tu, Y; Han, B; Shimizu, Y; Inoue, K; Fukui, Y; Yano, M; Tanii, T; Shinada, T; Nagai, Y
Abstract: Ion implantation through nanometer-scale apertures (nano-apertures) is a promising method to precisely position ions in silicon matrices, which is a requirement for next generation electronic and quantum computing devices. This paper reports the application of atom probe tomography (APT) to investigate the three-dimensional distribution of germanium atoms in silicon after implantation through nano-aperture of 10 nm in diameter, for evaluation of the amount and spatial distribution of implanted dopants. The experimental results obtained by APT are consistent with a simple simulation with consideration of several effects during lithography and ion implantation, such as channeling and resist flow.